A multiferroic iron arsenide monolayer. Issue 5 (15th February 2022) - Xuan, Xiaoyu; Yang, Tingfan; Zhou, Jian; Zhang, Zhuhua; Guo, Wanlin
Abstract : A highly stable iron arsenide monolayer material is predicted to exhibit ferroelasticity and magnetism simultaneously. Abstract : Iron arsenide (FeAs) monolayers are known as a key component for building iron-based superconductors. Here, we predict by first-principles calculations that the FeAs monolayer is a highly stable and multiferroic material with coexisting ferroelasticity and antiferromagnetism. The ferroelasticity entails a reversible elastic strain of as large as 18% and an activation barrier of 20 meV per atom, attributed to a weak hybridization between Fe d and As p orbitals. The local moments of Fe atoms are oriented out-of-plane, so that the magnetic ordering is weakly coupled to the structural polarization. Interestingly, fluorination of the FeAs monolayer can align the local moments in parallel and reorient the easy axis along the in-plane direction. As such, the fluorinated FeAs monolayer is potentially a long-sought multiferroic material that enables a strong coupling between ferroelasticity and ferromagnetism.